Resipatisme: A psychoeducation to reduce the tendency of klithih behavior in adolescents - Oktavia, Detty Putri Pratiwi; Zulhida, Nur Azmi; Rachim, Laila; Affan, Ahmad; Fitrianingsih, Wulan Suci; Kushartati, Sri (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Klithih, a Javanese term, was originally an ordinary night stroll without a clear purpose. Klithih becomes an act of violating the law if it is accompanied by aggressive or violent behavior. In recent years, klithih cases in Yogyakarta have increased and become public attention, with almost the average perpetrators being students. This study aimed to reduce aggressive behavior in adolescents with a tendency to klithih behavior by developing Resipatisme, a psychoeducation intervention consisting of emotion regulation, empathy, assertiveness, and altruism. A quasi-experimental quantitative method, with one group pretest-posttest design, was applied in this study. An aggressive behavior scale was used to collect the data. The Wilcoxon Signed Rank Test was applied to compare the data before (pretest) and after (posttest) intervention. The results show a significant difference between pretest scores and posttest scores. This finding implies that Resipatisme psychoeducation can reduce aggressive behavior in adolescents. Therefore this psychoeducation may be applied to prevent the tendency of klithih behavior.